Restartup : a founder's guide to crisis navigation - Krishnakumar, Arunkumar; Jia Ying, Maxson Tee (John Wiley & Sons Ltd, 2021)
"During a market boom, even bad startups can find funding. However, when a crisis hits, funds dry up, and very few startups will survive. However, with the appropriate tools, it is possible not just to navigate an economic crisis, but to embrace it, identify opportunities, and emerge stronger on the other side. In the current climate of economic instability, and with the financial impact of the coronavirus yet to fully bite, startups and entrepreneurs need solid, practical advice to help them keep their businesses alive--and even thriving."--